The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.5130/ijcre.v10i1.4947
|View full text |Cite
|
Sign up to set email alerts
|

From community data to research archive: Partnering to increase and sustain capacity within a native organization

Abstract: Expanding interest in community engagement and participation in research by universities, researchers, community members and funders reflects a dramatic paradigm shift in the way that we understand the research enterprise. In this article, we share our experience of a collaborative project between a non-profit membership organisation and researchers from two universities. We focus on the importance of infrastructure development for moving towards truly equitable partnerships that expand forms of participation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…The capacity of academic researchers and the institutional environment of the university are essential for developing community-university relations for research (Page-Reeves et al, 2017). There is a need to recognise and support research capacity in USC for establishing successful research relations (Goytia et al, 2013).…”
Section: Analysis Of South African Universitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The capacity of academic researchers and the institutional environment of the university are essential for developing community-university relations for research (Page-Reeves et al, 2017). There is a need to recognise and support research capacity in USC for establishing successful research relations (Goytia et al, 2013).…”
Section: Analysis Of South African Universitiesmentioning
confidence: 99%
“…The research conducted by Page-Reeves et al (2017) found that universities' community relations assisted to integrate research and action and those studies focussing on issues identified as priorities by USC. In education research, knowledge co-constructed through a deliberative process of dialogue with stakeholders has been shown to increase meaningful intergenerational involvement and positively impact to education (Bang et al, 2010).…”
Section: Analysis Of South African Universitiesmentioning
confidence: 99%
“…However, challenges to including patient stakeholders as active, integrated members of a research team remain. Creating capacity for engaged research requires the development of collaborative work relationships and new ways of thinking about the role of university resources and infrastructure (8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%